(untitled) (The Pakistan Development Review, 2012)
The accumulation of external debt is common phenomenon of the developing countries and it has become a common feature of the fiscal sectors of most of the economies. A country with lower saving rate needs to borrow more to finance the given rate of economic growth. So external debt is obtained to sustain the growth rate of the economy, which is otherwise not feasible with the given domestic resources. Pakistan is one of the developing countries and faces serious debt problems, according to World Bank Report 2000-2001, Pakistan is among the Highly Indebted Countries (HICs); because Pakistan’s present and future debt situation is very grim. According to the World Bank total external debt may be defined as debt owed to non-resident repayable in terms of foreign currency, goods or services. External debt is the composition of long term debt (public and publicly guaranteed debt plus private non guaranteed debt), short term commercial debt and International Monetary Fund (IMF) loans. Prior to early 1970s the external debt of developing countries was primarily small and official phenomenon, the majority of creditors being foreign governments and international financial institutions offer loan for development project [Todaro (1988)]. At the same time current account deficit was common which increased the external indebtedness of the developing countries, until when Mexico, despite an oil exporter, declared in august, 1992 that it could not services its debt ever since, the issue of external debt and its servicing has assumed critical importance and introduced the debt crises debate [Were (2001)].